2013
DOI: 10.1111/bcpt.12135
|View full text |Cite
|
Sign up to set email alerts
|

TRPV4-Mediated Calcium Influx and Ciliary Activity in Human Native Airway Epithelial Cells

Abstract: The transient receptor potential vanilloid 4 (TRPV4) is a calcium permeable ion channel expressed in airway epithelial cells. Based on studies of cell lines and animals, TRPV4 has been suggested to play a role in the regulation of ciliary beat frequency (CBF). Whether the same is true for human ciliated epithelial cells is not known. Therefore, the aim was to examine the expression and function of TRPV4 in human native nasal epithelial cells. Expression of TRPV4 mRNA in nasal epithelial cells and in the cell l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
36
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 21 publications
5
36
0
1
Order By: Relevance
“…This suggests involvement of TRPV1 in sensing LPS and neurogenic inflammation [85]. Moreover, using recombinant TRP expression in HEK293T cells, Alenmyr and colleagues demonstrated that, in addition to TRPA1 and TRPV1, LPS weakly activated TRPM3 and TRPM8 to promote calcium influx [86]. It should be noted that other studies have demonstrated expression of TLR4 in a subclass of TRPV1 containing trigeminal nociceptors and that LPS sensitized TRPV1 via TLR4-mediated signaling [87,88].…”
Section: Lps Recognition By Trp Channelsmentioning
confidence: 97%
See 1 more Smart Citation
“…This suggests involvement of TRPV1 in sensing LPS and neurogenic inflammation [85]. Moreover, using recombinant TRP expression in HEK293T cells, Alenmyr and colleagues demonstrated that, in addition to TRPA1 and TRPV1, LPS weakly activated TRPM3 and TRPM8 to promote calcium influx [86]. It should be noted that other studies have demonstrated expression of TLR4 in a subclass of TRPV1 containing trigeminal nociceptors and that LPS sensitized TRPV1 via TLR4-mediated signaling [87,88].…”
Section: Lps Recognition By Trp Channelsmentioning
confidence: 97%
“…In addition to sensory neuronal TRP, a recent study has shown the presence of a non-neuronal TRP channel that can detect LPS; specifically, the TRPV4 channel in airway epithelium in mice can detect LPS [89]. TRPV4 is expressed in both murine and human airway epithelial cells [86,90]. Alipzar et al demonstrated that murine airway tracheobronchial epithelial cells (mTECs), when stimulated with LPS, induced calcium influx that was dependent on TRPV4 and independent of TLR4 [89].…”
Section: Lps Recognition By Trp Channelsmentioning
confidence: 99%
“…Considering that intracellular Ca 2+ is a key regulator of the CBF (8,29), we sought to identify whether P4 regulated CBF through the modulation of Ca 2+ signaling in oviductal ciliated cells. We found that P4 increased the intracellular concentration of Ca 2+ through a mechanism that required both the TRPV4 channel, which produces Ca 2+ signals linked to CBF modulation (30)(31)(32)(33), and GABA receptors, which are the main inhibitory receptors in the mammalian central nervous system (34). GABAergic signaling involving the ligand-gated GABA A chloride channel and the metabotropic G i/o protein-coupled GABA B receptor has been found in epithelial tissues (35)(36)(37).…”
Section: Introductionmentioning
confidence: 92%
“…If this model holds true, inhaled TRPV4 blockers may represent a new class of bronchodilator drugs. The possible link between TRPV4 and COPD is also gaining strength: TRPV4 is expressed in murine and human airway epithelial cells, where it is believed to play a key role in mucociliary clearance by regulating ciliary beats (Lorenzo et al, 2008;Alenmyr et al, 2014). Impairment of this airway protective function by toxic inhalants (Li et al, 2011b) and/or carrying a gain-of-function TRPV4 variant ) is thought to increase the risk for developing COPD.…”
Section: B Transient Receptor Potential Channels Inmentioning
confidence: 99%